The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph18010270
|View full text |Cite
|
Sign up to set email alerts
|

Basic Public Health Service Utilization by Internal Older Adult Migrants in China

Abstract: Since 2009, the Chinese government has launched a basic public health services (BPHS) equalization program to provide the same BPHS to all the citizens. However, utilization of BPHS among older migrants is still low. The purpose of this paper was to explore the determinant individual and contextual factors of older migrants’ utilization of BPHS, and to provide suggestion for the government to improve BPHS utilization. Based on Andersen’s model of health services use, data from the China’s Regional Economic Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
0
20
0
2
Order By: Relevance
“…Different from local elderly, migrant elderly generally have low socioeconomic status and cannot enjoy the same social benefits as local residents; they are also less likely to have access to comprehensive health care [4]. Most migrant elderly are less willing to seek medical care, which could be detrimental to their physical and mental health and cause a range of health problems [5]. Compared with the local elderly, the MEFC are far away from their hometown, and their social network and social supports become weaker [6].…”
Section: Introductionmentioning
confidence: 99%
“…Different from local elderly, migrant elderly generally have low socioeconomic status and cannot enjoy the same social benefits as local residents; they are also less likely to have access to comprehensive health care [4]. Most migrant elderly are less willing to seek medical care, which could be detrimental to their physical and mental health and cause a range of health problems [5]. Compared with the local elderly, the MEFC are far away from their hometown, and their social network and social supports become weaker [6].…”
Section: Introductionmentioning
confidence: 99%
“…Academic research on human urbanization covers many fields, but traditional studies have focused on the household registration (hukou) system and the urban status of migrant people [ 16 ]. In recent years, the issue of human cognitive differences has also gradually gained attention [ 17 ]; for example, public health service utilization [ 18 ], educational assortative mating in marriage [ 19 ], and risk information-seeking behavior [ 20 ]. Through a literature review, this study found that elderly migrants reflect various cognitive characteristics of production and living needs.…”
Section: Literature Review and Research Methodsmentioning
confidence: 99%
“…The potential participants are informed by issuing leaflets, posting posters, calling through the telephone, and using other methods within the community. Recently, results showed that the percentage of migrant older adults receiving free medical checkups was 36.2% (15). Therefore, our study selected free health checkups as the measurement of basic public health services.…”
Section: Utilization Of Basic Public Health Servicesmentioning
confidence: 99%
“…In contemporary society, an increasing number of families are migrating with their elderly members to look after children, find jobs, or access better healthcare services in China. In addition, most of these elderly members are more than 60 years old (15). Strengthening the utilization of primary healthcare facilities is considered an effective approach to providing affordable, equitable access to quality basic health care for all Chinese citizens by 2020, as was pledged by China (13,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation